Index to social sciences & humanities proceedings. - Institute for Scientific Information ([Philadelphia] Institute for Scientific Information.)
Quarterly, with annual cumulation. Listing of published proceedings (consisting of papers presented) of conferences, seminars, symposia, colloquia, conventions, and workshops. Proceedings published in any format are included; those consisting only of abstracts are excluded. Besides the main section of contents of the published proceeding titles, there are indexes by category, author/editor, sponsor, location, subject, and corporate body.
Issues for 1979- published in 2 or more vols.
Keywords: Social sciences -- Indexes -- Periodicals; Humanities -- Indexes -- Periodicals; Congresses and conventions -- Indexes -- Periodicals; Humanities -- Bibliography; Humanities -- Congresses; Humanities -- Directory; Social Sciences -- Bibliography; Social Sciences -- Congresses; Social Sciences -- Directory